Adaptive fault tolerant control for hypersonic flight vehicle system with state constraints. Issue 14 (September 2020) - Peng, Zhiyu; Qi, Ruiyun; Jiang, Bin
Highlights: A fault-tolerant control scheme is proposed for HFVs with flexible dynamics, parameter uncertainties, faults and state constraints. The proposed method transforms the MIMO model properly such that the BLF based control design can be successfully employed to solve the problem of state constraints. Considering two types of actuator faults, an adaptive fault compensation mechanism is introduced to the BLFs-based controller. Abstract: In this paper, an adaptive fault tolerant control (FTC) scheme based on barrier Lyapunov functions (BLFs) for the hypersonic flight vehicle (HFV) with state constraints is proposed. Complexities of the aerodynamical uncertainties, external disturbances and flexible dynamics are taken into account in the controller design process. The paper deals with the MIMO system properly so that the backstepping technique based on BLFs can be successfully used for the issue of state constraints without neglecting the coupling of HFV system. To aim at the unknown faults of the elevators, an adaptive FTC mechanism is introduced to the BLFs-based controller, which increases the reliability of the system. Finally, simulations are conducted to verify the validity of the designed controller.